Effect of Nutritional Ingredients on Disease Activation in Psoriatic Arthritis - Varkal, Gizem; Akarca, Neşeriz Nihal; Türk, İpek; Yetişir, Ayşegül; Mete, Burak (Archives of Rheumatology, 2025)
Background/Aims: To investigate the relationship between food composition and patterns and disease activity in psoriatic arthritis (PsA) patients. Materials and Methods: This cross-sectional study evaluated patients with PsA (n = 73). Sociodemographic and disease-related parameters, including the duration of illness, Disease Activity Index for PsA (DAPSA), C-reactive protein, erythrocyte sedimentation rate (ESR), the Health Assessment Questionnaire (HAQ), and Mediterranean Diet Compatibility Scale were assessed. Nutrient intake was recorded over 3 days and analyzed using a standard nutritional analysis program. Processed food consumption was classified according to the NOVA system. Results: Among the patients with PsA, 71.2% of patients were female, 42.5% were obese, and 72.6% had low adherence to the Mediterranean diet (MD). The body mass index (BMI) and HAQ scores were higher in those with moderate-severe disease (DAPSA ≥ 15) than in those in remission or with mild disease (DAPSA ≤ 14) (P = 0.006 and P = 0.008, respectively). The MD adherence score was negatively correlated with the DAPSA, HAQ, and ESR (P = .025, P = .015, and P = .006, respectively). Higher adherence to the MD was associated with a lower risk of moderate-to-severe disease, while increases in cholesterol intake, sodium intake, and BMI were associated with a higher risk of disease severity. Conclusion: Obesity negatively affects disease progression in PsA. A protein-rich and a low-sodium diet appear to support remission, while poor adherence to the MD and high cholesterol intake may contribute to increased disease activity. These findings emphasize the importance of nutrition in the clinical course of PsA. Cite this article as: Varkal G, Akarca NN, Türk İ, Yetişir A, Mete B. Effect of nutritional ingredients on disease activation in psoriatic arthritis. Arch Rheumatol. 2025;40(4):459-464.